INDONESIA'S LAW NO. 4 OF 2023 AND CONSUMER PROTECTION IN DIGITAL FINANCIAL SERVICES: ASEAN LITERACY FRAMEWORK’S PERSPECTIVE - Albar, Rafsi Azzam Hibatullah; Karo Karo, Rizky; Nindyatami, Pawestri (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2022)
In January 2023, the Indonesian government passed Law No. 4 of 2023 on the Development and Strengthening of the Financial Sector (P2SK Law). Replacing more than 30 provisions, the law covers lots of topics including digital financial services (DFS) and consumer protection. A big contributing factor to this is the prevalence of the financial technology (FinTech) industry that utilises DFS. Digital financial literacy (DFL) is an important component to consumer protection in DFS since P2SK Law and other legal instruments recognize the importance of the consumer’s own awareness when using DFS. The Alliance for Financial Inclusion (AIF) and ASEAN Working Committee on Financial Inclusion (WC-FINC) issued a policy note in 2020 on DFL in the region. Expected to guide ASEAN member states in formulating their policies through a framework that includes four key actions. This research aims to inspect the direction in which the Indonesian government is heading with regard to its consumer protection in DFS after the enactment of the P2SK Law from ASEAN’s DFL-leaning standpoint. It can be concluded that Indonesia, mainly through Bank Indonesia and the Financial Services Authority (OJK) has been a big advocate of financial literacy, including DFL, as a proponent of consumer protection in recent years. Among other things, P2SK Law further affirms this by connecting stakeholders and embedding DFL at the core of Indonesia’s national strategies.